Riding for beginners - Binder, Sibylle Luise; Wolf, Gefion (New York : Sterling Pub., 1998)
Includes information on how and where one can learn to ride a horse, how horses think, the right way to care for and train a horse, and the requirements for becoming a good rider.
Includes index.
Keywords: Horsemanship -- Juvenile literature; Horses -- Juvenile literature; Horsemanship; Horses